Content validity and ePRO usability of the BPI-sf and "worst pain" item with pleural and peritoneal mesothelioma - Heather L. Gelhorn; Sonya Eremenco; Anne M. Skalicky; Zaneta Balantac; Tricia Cimms; Katarina Halling; Chris Sexton (SpringerOpen, 2018)
Abstract Background The Brief Pain Inventory-short form (BPI-sf) is widely used in self-reported pain assessment, incorporates pain numeric rating scales (NRS) and is commonly utilized in electronic format in clinical trials, however, there is no published information about its usability as an electronic patient-reported outcome (ePRO) measure. The objective of this qualitative study was threefold: 1) to better understand pain experiences among patients with pleural or peritoneal mesothelioma; 2) to assess the interpretability of the instructions, item stem, recall period, and response option of the "worst pain" item of the BPI-sf; and 3) to examine the usability of the TrialMax Touch™ (CRF Health, Inc., Plymouth Meeting, PA) screen-based handheld device and the electronic format of the BPI-sf in a sub-sample of pleural mesothelioma patients. Methods A cross-sectional qualitative study was conducted among participants with pleural and peritoneal mesothelioma recruited from 4 clinical sites in the US. Semi-structured telephone or in-person interviews were conducted consisting of concept elicitation, cognitive interviewing of the 11-item BPI-sf, and in-person interview evaluation of ePRO assessment usability in pleural mesothelioma patients. Results Twenty-one participants recruited from 4 clinical sites in the US were interviewed in-person (n = 9) and by telephone (n = 12); 71% male; mean age 68.7 ± 13.6 years. Pleural and peritoneal patients described pain as ranging from discomfort to intense pain and reported being able to distinguish tumor pain from treatment pain. The BPI-sf "worst pain" item was relevant to, and easily understood by, study participants with pleural and peritoneal mesothelioma. The ePRO version was found to be easy to use, but readability of small font may be an issue. Participants reported minimal differences between their responses on the paper and ePRO version for all of the pain severity and pain interference items. Conclusions Results support the relevance and ease of understanding of the "worst pain" item and provide support for its content validity in patients with pleural and peritoneal mesothelioma. Usability of the ePRO format of the BPI-sf was confirmed for use in clinical trials among patients with pleural mesothelioma.